Pengaruh Kecerdasan Emosional dan Kecerdasan Spiritual Terhadap Tingkat Pemahaman Akuntansi pada Mahasiswa Akuntansi STIE STEKOM - Supriadi, Supriadi; Munifah, Munifah (Jurnal Riset Manajemen dan Akuntansi, 2026)
This study aims to examine and analyze the influence of Emotional Intelligence (X₁) and Spiritual Intelligence (X₂) on the Level of Accounting Understanding (Y) among Accounting students at STIE Modern STEKOM. Data were collected through questionnaires distributed to 74 respondents, the majority of whom were female (62%) and within the productive age range of 17–30 years (82%). Data quality tests indicated that the research instruments were valid and reliable. Multiple Linear Regression Analysis produced the following regression model: Y = 5.987 + 0.745X₁ + 0.549X₂ + e. Partially (t-test), Emotional Intelligence (t = 3.987; Sig. = 0.004) and Spiritual Intelligence (t = 2.356; Sig. = 0.010) were found to have a positive and significant effect on the Level of Accounting Understanding. Simultaneously (F-test), both independent variables had a significant influence (F = 12.567; Sig. < 0.001). The adjusted coefficient of determination (Adjusted R²) of 0.524 indicates that 52.4% of the variation in the Level of Accounting Understanding is explained by Emotional Intelligence and Spiritual Intelligence. The study concludes that strengthening students’ emotional and spiritual aspects is essential to optimize their understanding of accounting materials.